Teachers' perceptions on student evaluation of teaching as a tool for faculty development and quality assurance in medical education - Asitava Debroy; Abhishek Ingole; Abhay Mudey (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Student evaluation of teaching (SET) is considered to be one of the most important as well as inexpensive resources for sustaining professional development in medical teaching. The aim of this project was to improve the quality of education in our medical college by using student feedback as a tool for faculty development. However, it is also important to obtain teachers' perceptions on SET. MATERIALS AND METHODS: This was an educational research study conducted on a single practical/tutorial batch of fourth-semester students in pathology chosen by random selection. Feedback regarding teaching was collected for all the teachers in the department of pathology where the students had to rate the teachers on a scale of 1-5. Teachers' perceptions on students' feedback were gathered with the help of another structured prevalidated questionnaire containing 15 questions/items. The feedback data were obtained using a 5-point Likert scale. The scores obtained from the students' evaluation data and the teachers' perception data on the different items were analyzed using SPSS software version 20.0. RESULTS: Significant findings from students' feedback were that 80% of teachers had a median score of >4 in explicit curriculum, indicating that most of the students agreed that the teachers teach their core subject well. However, only 20% of teachers had a median score >4 in implicit curriculum. Teachers, in their feedback, fully agreed that students should be involved in the evaluation of teachers and that student feedback ensures the overall faculty development in the institute and can be used as a tool for quality assurance in medical education. CONCLUSION: Students' feedback is one of the best methods of evaluation of teachers to ensure the overall faculty development and quality assurance in medical education. Thus, a regular feedback mechanism should be in place for the entire institution.